Dynamic Evolution of the Type of “meideshuo” Discourse Marker and Its Metapragmatic Functions - Meijun, Luo (Sinología hispánica. China Studies Review, 2017)
A type of “meideshuo” discourse markers contains three subtypes: “meideshuo”, “meihuashuo”, and “meishuode”. From the point of view of semantic-pragmatics, this type of discourse markers evolves dynamically from the meaning of “no words to say” to “positive meaning”, and finally evolves to a discourse marker. The metapragmatic functions of the discourse markers are new information focused, proposition affirmed, and communicative purpose predicted. The process of the discourse marker evolution is not only the process of lexicalization and grammaticalization, but also the process of intersubjectification. The pragmatic extensions and semantic entailment are contributed to function as motivations for the dynamic evolution of “meideshuo” discourse markers.